Alström syndrome is associated with short stature and reduced GH reserve. (26th March 2013) - Romano, S.; Maffei, P.; Bettini, V.; Milan, G.; Favaretto, F.; Gardiman, M.; Marshall, J. D.; Greggio, N. A.; Pozzan, G. B.; Collin, G. B.; Naggert, J. K.; Bronson, R.; et al.
Summary: Introduction: Alström syndrome (ALMS) is a rare autosomal recessive monogenic disease included in an emerging class of genetic disorders called 'ciliopathies' and is likely to impact the central nervous system as well as metabolic and endocrine function. Individuals with ALMS present clinical features resembling a growth hormone deficiency (GHD) condition, but thus far no study has specifically investigated this aspect in a large population. Material and Methods: Twenty‐three patients with ALMS (age, 1–52 years; 11 males, 12 females) were evaluated for anthropometric parameters (growth charts and standard deviation score (SDS) of height, weight, BMI), GH secretion by growth hormone–releasing hormone + arginine test (GHRH‐arg), bone age, and hypothalamic–pituitary magnetic resonance imaging (MRI). A group of 17 healthy subjects served as controls in the GH secretion study. Longitudinal retrospective and prospective data were utilized. Results: The length‐for‐age measurements from birth to 36 months showed normal growth with most values falling within −0·67 SDS to +1·28 SDS. A progressive decrease in stature‐for‐age was observed after 10 years of age, with a low final height in almost all ALMS subjects (>16–20 years; mean SDS, −2·22 ± 1·16). The subset of 12 patients with ALMS tested for GHRH‐arg showed a significantly shorter stature than age‐matched controls (154·7 ± 10·6 cm vs 162·9 ± 4·8 cm, P  = 0·009) and a mild increase in BMI (Kg/m 2 ) (27·8 ± 4·8 vs 24·1 ± 2·5, P  = 0·007). Peak GH after GHRH‐arg was significantly lower in patients with ALMS in comparison with controls (11·9 ± 6·9 μg/l vs 86·1 ± 33·2 μg/l, P  < 0·0001). Severe GHD was evident biochemically in 50% of patients with ALMS. The 10 adult ALMS patients with GHD showed a reduced height in comparison with those without GHD (149·7 ± 6·2 cm vs 161·9 ± 9·2 cm, P  = 0·04). MRIs of the diencephalic and pituitary regions were normal in 11 of 12 patients. Bone age was advanced in 43% of cases. Conclusions: Our study shows that 50% of nonobese ALMS patients have an inadequate GH reserve to GHRH‐arg and may be functionally GH deficient. The short stature reported in ALMS may be at least partially influenced by impairment of GH secretion.